Nuclear β-decay half-lives in the relativistic point-coupling model. (22nd February 2016) - Wang, Z Y; Niu, Y F; Niu, Z M; Guo, J Y
Abstract: The self-consistent proton–neutron quasiparticle random phase approximation approach is employed to calculate β -decay half-lives of neutron-rich even–even nuclei with . A newly proposed nonlinear point-coupling effective interaction PC-PK1 is used in the calculations. It is found that the isoscalar proton–neutron pairing interaction can significantly reduce β -decay half-lives. With an isospin-dependent isoscalar proton–neutron pairing strength, our results well reproduce the experimental β -decay half-lives, although the pairing strength is not adjusted using the half-lives calculated in this study.